Enhancing Public Health Through Free Health Screening for the Elderly and Blood Donation: A Model for Sustainable Community Engagement - Ahmad Sudrajat, Yusuf; Tulloh, Ayu Hidayah; Sabrianti, Nanda Putri; Rahayu, Nur; Fitriansyah, Annas Hanifan; Hakami, Muhammad Emran (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
This study aims to assess the impact of a free health screening program for the elderly and a blood donation drive in enhancing public health awareness and community engagement. The increasing prevalence of non-communicable diseases among the elderly and the high demand for blood donations underscore the need for such initiatives. The study employed a community-based intervention approach, incorporating health screenings for 40 elderly participants and a blood donation drive involving 45 donors. The methodology included medical assessments, surveys, and observational data collection. Findings indicate that 35% of elderly participants were diagnosed with hypertension, 20% with elevated blood glucose levels, and 10% with high uric acid levels. Furthermore, 80% of blood donors expressed willingness to participate in future donation activities. Nutritional support, including whole wheat bread and mung bean extract for the elderly and iron supplements with isotonic beverages for blood donors, was provided to aid recovery and promote healthy habits. These results highlight the significance of integrated healthcare initiatives in fostering preventive health practices and increasing voluntary blood donations. The study suggests expanding the scope of health screenings and strengthening digital outreach to enhance public participation. Future research should involve larger sample sizes to validate these findings and explore additional factors influencing health awareness and donor retention. Overall, this study provides valuable insights into the effectiveness of community-driven health programs in promoting sustainable healthcare practices.